1H NMR-based metabolomic fingerprinting to determine metabolite levels in serrano peppers (Capsicum annum L.) grown in two different regions. (December 2017) - Becerra-Martínez, Elvia; Florentino-Ramos, Elideth; Pérez-Hernández, Nury; Gerardo Zepeda-Vallejo, L.; Villa-Ruano, Nemesio; Velázquez-Ponce, Manuel; García-Mendoza, Felipe; Bañuelos-Hernández, Angel E.
Abstract: Chili pepper ( Capsicum annuum ) is the most important and emblematic condiment in Mexican food. Serrano pepper is a variety of C. annuum that is traditionally cultivated in Mexico and commercialized in local markets. The aim of this study was to describe the 1 H NMR metabolomic profiling of the aqueous phase of serrano peppers harvested from two distinct regions, in the states of Veracruz and Oaxaca, Mexico. According to the current results, aspartate citrate, lactate, leucine and sucrose were found at higher amount in the serrano peppers from Veracruz. On the other hand, acetate, formate, fumarate, malonate, phosphocholine, pyruvate and succinate showed the highest abundance in this product from Oaxaca. These are the main metabolites that distinguish one group from the other. The spectrometric method reported presently is characterized by great simplicity, robustness and reproducibility. Thus, this technique can be used for establishing reliable metabolomic fingerprints of serrano peppers grown under different environmental conditions. Graphical abstract: Highlights: Metabolic profile was used to discriminate between serrano peppers cultivated in Veracruz and Oaxaca, Mexico. Multivariate analysis showed a clear discrimination between two serrano peppers. Twelve metabolites contribute to the discernment between the two serrano peppers. Metabolite differences of two serrano peppers types using NMR can be economic implications.